COMPARISON OF THE IMPLEMENTATION OF MAQASHID SHARIA IN CERTIFIED SHARIA HOTELS AND UNCERTIFIED SHARIA HOTELS (STUDY ON SHARIA HOTELS IN INDONESIA) - Memed Sueb; Euis Nurhayati; Indri Yuliafitri (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) Universitas Islam Negeri (UIN), 2020)
The performance of Islamic entities does not only consist of aspects of financial performance (economic performance), but also views from the aspect of sharia as a characteristic that distinguishes it from conventional entities. The purpose of sharia is revealed in the form of maqashid sharia which must be applied in all aspects of life. Therefore, the maqashid sharia approach can be an alternative choice for assessing the performance of a sharia-based entity. In addition, another requirement for Islamic entities is to disclose Islamic Social Reporting (ISR), in which there are 43 items that are characteristic of Islamic entities that must be disclosed in the financial statements of Islamic entities as a form of accountability for Islamic entities. This research uses a qualitative approach by means of case studies based on the interpretive paradigm in order to capture the performance of Islamic hotels using the maqashid sharia approach, and to see whether the elements in Islamic Social Reporting already exist in Islamic hotels. Based on the results of a survey of sharia hotels in Indonesia, both those that have been certified as sharia hotels, hotels that have halal certification for their restaurants, and hotels that claim to be sharia hotels. The conclusion is that certified sharia hotels have been proven to have implemented and maintained sharia values in their hotel operations, although there were some insignificant violations. The implementation of sharia values is not only applied by sharia hotels that have been certified as sharia hotels. The new sharia hotels apply the halal concept, either claiming to be a sharia hotel in the name of the hotel or not mentioning the word sharia in the hotel name. In fact, there were almost perfect implementations in several Islamic hotels that were not yet certified as sharia hotels. It's just that for 2-star hotels and below that claim to be sharia hotels, the implementation of sharia values is only limited by not accepting guests who are not legal spouses, and not providing liquor.